Lecturers’ Engagement and Job Performance: Experiences from Kwara State Tertiary Institutions in Nigeria - Olubukola James, OJO; Busayo Oluwabukola, ALAO; Adedapo Adetiba, ATOLAGBE (Papers in Education and Development, 2024)
The study examined lecturers’ engagement and job performance in tertiary education institutions in Kwara state. A descriptive survey type was adopted as the research design, with a study being guided by two research questions, one of which was the main question and four operational hypotheses. The population consisted of all 14,000 lecturers in Kwara State tertiary institutions. The researchers used a purposive sampling technique to select 350 lecturers who were engaged in the four components, i.e., teaching, research, academic advising and administration, as the respondents for the study. The data collection instrument was a researcher-designed questionnaire. Descriptive statistics were employed to analyse the research questions, while inferential statistics was used to test all the hypotheses at 0.05 alpha level of significance. The study revealed that lecturers are more engaged in teaching, research, academic advising, and administration. The study recommends the need for robust measures to enhance lecturers’ engagement in tertiary institutions in Nigeria. Keywords: Lecturers’ engagement, teaching, research, academic advising, administration, job performance